Ecologia integrale e pluralismo etico-religioso (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Introduzione: per una transizione ecologica integrale - 2. La varietà dei modelli eco-culturali dei soggetti del pluralismo etico-religioso - 3. Le associazioni animaliste e lo stile di vita vegano - 4. Le comunità smart dell’economia collaborativa sostenibile - 5. Le imprese socialmente responsabili - 6. Le “società benefit” - 7. I domini collettivi e le cooperative di comunità nella gestione dei beni comuni - 8. La tutela dei siti naturali d’interesse culturale - 9. Le organizzazioni agresti di impegno sociale - 10. Il sostegno finanziario delle banche etiche allo sviluppo sostenibile - 11. Conclusione: un ulteriore impegno per l’ecclesiasticista.Integral ecology and ethical-religious pluralismABSTRACT: The contribution intends to attest the interest for the scholar of ecclesiastical law for the phenomenon of ecological transition, in which some confessional bodies, as well as groups, associations and communities of people who are differently oriented from the ethical-cultural point of view, driven by a resilience movement induced by the social and environmental crisis, they are involved in various ways. They, in pursuing what Pope Francis defined, in the encyclical Laudato si', “integral ecology”, combine attention to the protection of creation and the expression of the personality of man, through the implementation of initiatives based on a new development model.